Macroecologia e distribuição geográfica da tribo Bignonieae (Bignoniaceae) - Meyer, Leila (2019)
Understanding geographical patterns of species diversity and their underlying processes is one of the major goals of biogeography and macroecology. This thesis contributes to this topic as its main aim was to investigate patterns in the distribution of species richness of the tribe Bignonieae (Bignoniaceae), the largest clade of Neotropical lianas with almost 400 species. Comparing two hull methods used to build species ranges (i.e., convex hull and alpha hull) (Chapter 1), we found that both methods can be considered as equivalent for mapping species richness patterns. However, the alpha hull is a more conservative approach that tends to reduce the chance of species range overestimation in comparison to the convex hull. We found that species ranges and the overall Bignonieae richness pattern respond similarly to environmental and spatial variables (Chapter 2), which suggests that the same process are acting to determine both species ranges and species richness in Bignonieae. Nonetheless, some species attributes reduced the congruence in ranges and richness response, such as: (i) lack of extrafloral nectaries, (ii) small to medium range sizes, and (iii) late-diverging species. We also found that canopy height is a main driver of richness patterns of liana species of the tribe (Chapter 3), in addition to climate and soil variables. However, the relationship of liana richness and canopy height changes according to the habitat where species occur. Lianas from forest and riparian habitats increase in number in taller canopies, while savanna lianas increase in shorter canopies. We noticed the distribution of species richness of the tribe is associated with the current distribution of forest and savanna habitats in the Neotropics, with a great species accumulation in forest habitats such as the Amazon and the Atlantic rainforests.